Pengaruh Penggunaan Media Audio Visual Terhadap Hasil Belajar Siswa Pada Materi Mengidentifikasi Unsur-Unsur Cerita Anak Kelas V SD NEGERI Mannuruki Kecamatan Tamalate Kota Makassar - Ummu Khaltsum; Sofyan, Sofyan Khadafi; Syahruddin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This research aims to determine the effect of using Audio-Visual media on student learning outcomes in the material of identifying story elements for class V children at Mannuruki State Elementary School. This research is a type of quantitative research using a Quasi Experimental method with a nonequivalent control group design. The samples studied were fifth grade students at Mannuruki State Elementary School, Tamalate District, Makassar City, namely in the experimental group there were 22 students learning using Audio-Visual media, and in the control group there were 18 students learning without using Audio-Visual media. The data collection instruments used in this research were written tests in the form of essays, initial tests (pretest) and final tests (posttest) to measure student learning outcomes before and after the application of Audio-Visual media and documentation. The data analysis technique used is a descriptive analysis test and an inferential sample T test. Based on the results of this study, it shows that the average posttest score for the experimental group was 76.36 and the control group was 58.33. These findings are strengthened based on the results of hypothesis testing using the T-test showing that the condition for the results of t calculated > t table is 6.4839 > 2.0243 with the results of the hypothesis H1 being accepted. This proves that the use of Audio-Visual media has an effect on student learning outcomes in the material on identifying story elements for class V students at SD Negeri Mannuruki, Tamalate District, Makassar City.